A menace to human health: rhino-orbital cerebral mucormycosis - Sharma, Arvind; Bharti, Aditi; Singh, Tej Pratap; Sharma, Richa (International Journal Of Community Medicine And Public Health, 2021)
Collate and interpret data on rhino-orbital-cerebral mucormycosis (ROCM) infections admitted at the tertiary care centre and investigate the common contributing factors leading to such infections and highlighting the relationship of this upsurge seen in patients infected with COVID-19. We conducted a cross-sectional study in Central India, in the period of eleven days (from 9 May to 18 May). A total of ten patients with ROCM was investigated, admitted to the separate ward for mucormycosis in the tertiary care centre. A self-pre-designed questionnaire was used for the evaluation. Verbal consent was obtained from the patients before the start of the study and also ensured the confidentiality of their respective details. Among ten of the patients, six patients were known cases of diabetes mellitus, two of the patients were diagnosed with diabetes mellitus after the initiation of corticosteroid therapy during their treatment and two of them were non-diabetic. All the patients in this case series were on corticosteroid therapy and on oxygen supplementation. Majority of the patients showing mild to moderate disease with unilateral symptoms, although only 10% showed the severe disease with bilateral eye involvement. It is evident that the poor or impaired immune functioning is the leading cause of the upsurge in mucormycosis cases. Therefore, early diagnosis and treatment of fungal infections can substantially reduce morbidity and mortality.